Physicochemical characteristics, sensory profile, probiotic, and starter culture viability of synbiotic yogurt - Jaman, Sadia; Islam, Md Zakirul; Sojib, Md Shahriar Islam; Hasan, Md Sayed; Khandakar, Md Mehedi Hasan; Bari, Md Sadakatul; Sarker , Md Abid Hasan; Habib, Raihan; Siddiki, Mohammad Shohel Rana; Islam, Mohammad Ashiqul; Rashid, Md Harun ur (Journal of Advanced Veterinary and Animal Research, 2022)
Objectives: This study aimed to envisage the effectiveness of adding three particular prebiotics (inulin, β-glucan, and Hi-maize) to synbiotic yogurt’s physicochemical properties, sensory characteristics, and survivability of the probiotic and starter cultures. Materials and Methods: The yogurt’s gross composition, syneresis, water-holding capacity (WHC), viscosity, sensorial properties, and probiotic and starter cell stability were analyzed. The Lactobacillus delbrueckii subsp. bulgaricus M240-5 and Streptococcus thermophilus M140-2 were employed as yogurt starter bacteria, and Lactobacillus acidophilus LA-5 as probiotic culture. The synbiotic yogurt was formulated with 5% sucrose and 0.7% artificial vanilla flavor. Results: The findings showed that when prebiotic ingredients were added to synbiotic yogurt, it had a significant impact on its sensory qualities, WHC, syneresis, and viscosity when compared to plain yogurt samples. The prebiotics did not affect the pH and titratable acidity of the yogurt samples. Additionally, the prebiotic supplementation did not influence the protein and fat content of synbiotic yogurt (p < 0.05). Prebiotics had an impact on the probiotic cell viability and total viable count (p < 0.05) compared to the plain sample, the 2.5% β-glucan, 1.5% and 2.5% Hi-maize samples had the highest mean viability (8.95 Log CFU/ml). The starter culture ratio remained stable in response to the prebiotic levels. Conclusion: In summary, the production of synbiotic yogurts supplemented with Hi-maize and β-glucan at 1.5% and 2.5%, respectively, is highly advised because these supplementations provide yogurt with acceptable syneresis, viscosity, WHC, and sensory attributes. J. Adv. Vet. Anim. Res., 9(4): 694–701, December 2022 http://doi.org/10.5455/javar.2022.i638